Brazilian dental students' intentions and motivations towards their professional career - Dos Santos, Beatriz Ferraz [UNESP]; Nicolau, Belinda; Muller, Katia; Bedos, Christophe; Zuanon, Angela Cristina Cilense [UNESP] (My University, 2013)
Investigating career motivations and intentions of dental students provides a better understanding of their role in society and contributes to the debate on dental education and practices. This study describes the profile, career choice motivations, and career intentions of Brazilian dental students and evaluates factors related to these choices. A cross-sectional study was carried out among dental students from three Brazilian public universities (N=915), with a response rate of 83.7 percent. Students (N=766) responded to a self-administered questionnaire about sociodemographic factors, reasons for choosing dentistry as a career, and future career intentions. Job conception was found to be the main reason for choosing dentistry as a profession. Most students intended to become specialists and work in both the public and private sectors simultaneously. Female students (OR 2.23, 95 percent CI=1.62-3.08), low-income students (OR 1.86, 95 percent CI=1.10-3.13), and students beginning their program (OR 1.87, 95 percent CI=1.22-2.85) were more likely to work in the public and private sectors simultaneously than other types of students. This study suggests that choice of career and career plans are influenced by factors related to the students' characteristics and their conception of the profession. The opportunity to combine private and public dental practice may be viewed as a way to achieve income and job security.
Keywords: Brazil; Career choice; Dental students; Oral health care access; Oral health care workforce; Professional practice; adolescent; adult; behavior; cross-sectional study; curriculum; decision making; dental education; dental procedure; dental student; dentistry; female; health services research; human; male; manpower; motivation; organization and management; professional practice; psychological aspect; questionnaire; socioeconomics; statistical model; Adolescent; Adult; Career Choice; Cross-Sectional Studies; Curriculum; Dental Health Services; Female; Health Services Research; Humans; Intention; Logistic Models; Male; Motivation; Private Sector; Professional Practice; Public Sector; Questionnaires; Schools, Dental; Socioeconomic Factors; Specialties, Dental; Students, Dental; Young Adult